Patent Research and Its Relevance for Innovation Development - Kossko, T.G.; Pavlygo, T.M. (Science and Innovation, 2024)
The patent research in accordance with the world standards, as well as with the standards of the Russian Federation and Ukraine has been considered. The dynamics of patent activities in the National Academy of Sciences of Ukraine are reported.